“Presume not that I am the thing I was”: The Transformation of the Idea of the King and the Concept of Kingship in Shakespeare’s Henriad - Meriç Tutku Özmen (Ideas: Journal of English Literary Studies)
From 1584 to 1599, Shakespeare wrote two tetralogies of history plays covering the period from the reign of Richard II to Henry VII. As Elizabeth’s age (she was fifty-seven in 1590), her problematic right to the crown, and the fact that the crown would pass to the Stuart dynasty, whose Catholic members had previously been excluded as potential successors, unless the queen would leave an heir make history plays popular among the theatregoers in Shakespeare’s time. In his history plays, Shakespeare is concerned with the problems of rebellion, the divine right of kings, and the nature of kingship. In his portrayal of kings, the playwright is more concerned with the monarchs’ actions rather than their eloquent speeches. The king in each play, as well as several other characters, provides insight and embodies a different approach to the idea of an ideal monarch. Each king differs from the other in crucial ways and has unique weaknesses and strengths. The hardships of being a king and the responsibility it brings are central to these plays, and the soliloquies delivered by the characters draw attention to what actually makes a king or gives him the right to rule, a question that has been considered at key points throughout the sequence of the history plays. Hence, this paper aims to scrutinize the transformation of the idea of a king and the concept of kingship in Shakespeare’s Henriad, namely Richard II, Henry IV Part 1, Henry IV Part 2, and Henry V.